Location-Aware Recommendation Engines in Local Library Services - MuhamedAle, Hasssan; Ramesh, Krishnan; Punitha, K.; Rakhmanovich, Ibragimov Ulmas; Shavkidinova, Dilnavoz; Udayakumar, R. (Indian Journal of Information Sources and Services, 2025)
Integrating geolocation recommendation engines into local libraries is an achievement that improves user interactivity, access, and resource utilization. This research examines the application of geolocation technologies and customized recommendation systems to suggest real-time books, resources, or events to patrons based on their locations inside or outside the library. Libraries can create responsive user experiences using data like borrowing history, preferences, and location which helps in the discovery of materials that are not highly sought after. Such technologies also enable patrons, including those with disabilities, to receive guided search aids to specific shelves or sections which makes complex libraries easier to navigate. Moreover, these systems can assist in advertising localized events such as workshops, book readings, or community gatherings to patrons within a determined range. This paper analyzes the applicable literature addressed with Bluetooth beacons, RFID, GPS, and mobile applications with machine learning models. The critique analyzes privacy, data security, infrastructure expenses, and proffered recommendations for socially responsible implementation. This study found that location-aware recommendation systems transform library services and meet the shifting demands of contemporary users, transforming libraries into interactive, agile, and integrative spaces. Such automated customization can greatly enhance the public’s interest in libraries as enduring resources for learning within the community.